VALUES OF ISLAMIC EDUCATION IN ABU UMAR BASYIER'S SANDIWARA LANGIT - MASTHUR, M. SYAKIR (2010)
The first fact that appeared on earth when Gabriel came to The Prophet for the first time was that the new religion (Islam) was based on science and rejected false beliefs and delusions as a whole. In the same manner as science, education is very important in Islam Method of teaching has very important role in education and narrating story was one of the Prophet's methods. This narrating method was then followed by Muslim scholars and educators from earlier age till now, and one of them is Abu Umar Basyier who wrote Sandiwara Langit that assumed to have some values of Islamic education. The problem statement of this research is: "what values of Islamic education are contained in Abu Umar Basyier's Sandiwara Langit?" and the objective of this study is to determine the values of Islamic education contained in Abu Umar Basyier's Sandiwara Langit. This study is expected to give contributions of thought to the development of science, particularly the development of Islamic education, in the form of strengthening the theory that narrating story is a teaching method, and expected to be able to teach the general public, especially educators among the Muslims, that there are many lessons can be studied from a story and encourage Muslims educators that narrating story as one of the main educational methods. This research is a qualitative one because it produces descriptive data and it is a library and documentation research for the data observed are library texts and documents. The primary data source of this research is Abu Umar Basyier's Sandiwara Langit. The technique of collecting data in this study is documentation and the techniques of the analyzing data are descriptive and inductive technique. In Sandiwara Langit, it can be found values of Islamic education. Those are honesty, courage, peaceability, self-reliance, self-discipline and moderation, self-purity, loyalty and trust, respect, love, empathy, hospitality, and value of justice and generosity. The value of honesty in the story includes honesty to others, honesty to an institution and honesty to oneself. The value of courage in the story includes the courage to oppose the majority that leads to the wrong path, the courage to attempt good deed although it is difficult, and the courage to say "no" to a demand that leads to the wrong. The value of peacebility the story is controlling the emotion. The value of self-reliance in the story is value of being independent. The value of discipline and moderation in the story are the ability to manage self-emotion and desire and the ability to manage time. The value of purity in the story includes the purity of the soul (from loving affairs of mortal life) and awareness to keep the purity itself before and after getting married. The values of loyalty and trust that are in the story include loyalty to the profession and institution, loyalty to the family, and being consistent to the promise. The value of respect that can be found is respect to the other. The value of love in the story includes love for family, love for couple, love for another Muslim brother, and love for Allah.The value of empathy in the story includes empathy to other people financial condition. The value of hospitality in the story includes hospitality to the guest. The value of justice in the story includes justice to the family, the understanding of generosity and the understanding of forgiveness.